Oncolytic adenovirus-loaded menstrual mesenchymal stem cells overcome the blockade of viral activity exerted by ovary cancer patients' ascites - Alfano, Ana Laura (2017)
Ovary cancer patients present peritoneal ascites at recurrence as a marker of disseminated disease and dismal prognosis. Oncolytic immunotherapy is an emerging approach for the treatment of disseminated cancer. In the present work we show the construction of a novel oncolytic adenovirus, AR2011, to target malignant ovary tumors. The survival curves were made by infecting malignant cells with AR2011 at different MOIs and showed that AR2011 exhibited a clear lytic effect in vitro in human ovary cancer cell lines and malignant cells obtained from ovary cancer patients´ ascitic fluids (AFs). By mixed the oncolytics adenovirus and crescent dilutions of AFs we demonstrated that AR2011 activity was neutralized by antibodies present in 31 samples of patients´-derived AFs. However, this blockade was overridden by preloading menstrual blood stem cells (MenSC) with AR2011 (MenSC-AR) since under these conditions AFs exerted no in vitro inhibitory effect on viral lytic activity. We performed cytokines and chemokines arrays of AF to study the composition of the factors present in the patient samples. Moreover, we perfomormed migration assays and observed that soluble factors present in AFs act as MenSC chemoattractants. MenSC-AR treatment of nude mice carrying established peritoneal carcinomatosis following administration of human ovarian cancer cells was able to inhibit tumor growth at levels similar to those observed with AR2011 alone. This study demonstrates that MenSC can be used to override the blockade that ascitic fluids exert on viral oncolytic effect.